The Intention to Use of a New Mobile Apps: A Case from Customers of an Indonesian Electrity Company - Eriyandini, Andhita; Ekawati, Ardhianiswari Diah (Syntax Literate, 2024)
Mobile apps are now an integral part of our daily life which brought quite significant changes in consumer behavior. Therefore, the development of electronic service quality becomes a crucial factor to consider in determining whether digital transformation affects customer satisfaction. PT PLN (Persero), the Indonesian Electricity Company launched their new mobile apps in 2022 with the objective to provide better customer engagement and service. New PLN Mobile is an application used by PT PLN (Persero) to facilitate customers in enjoying every service provided by the company. This study integrates constructs from the mobile-technology acceptance model (M-TAM) and unified theory of acceptance and use of technology model (UTAUT) into a new theoretical model and tests them to a one of rural regions in Indonesia. The study was conducted by using a structured questionnaire to collect data from 566 respondens of customers of PT PLN (Persero) PLN ULP Jeneponto. The research model was assessed using the partial least squares structural equation model (PLS-SEM) methodology, facilitated by the Smart PLS software to provide insights into the factors that determine the acceptance of technology, which can explain user behavior. The analysis results are expected to identify the factors of customer readiness in adopting the New PLN Mobile electronic service in Jeneponto Regency. The results revealed significant relationships for all of the hypotheses. Mobile Usefulness to Intention to Use (H1), Mobile Ease of Use to Intention to Use (H2), Social Influence to Intention to Use (H3), Facilitating Condition to Intention to Use (H4) and Intention to Use to Actual Use (H5) showed t-stat values respectively, surpassing the standard test value. In the results, it can also be observed that the most significant factor influencing Intention to Use is Facilitating Condition.